The Florida Right to Farm Act - Jana Caracciolo; Raychel Thomas; Catherine G. Campbell (EDIS)
Every state has a right to farm act, but the ways in which these acts affect farming operations differ from state to state. This publication is designed to provide an accurate and current summary of the Florida Right to Farm Act. Written by Jana Caracciolo, Raychel Thomas, and Catherine Campbell, and published by the UF/IFAS Department of Family, Youth and Community Sciences, July 2021.